2014
DOI: 10.1108/jeim-05-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the commercial value of social networks

Abstract: Purpose – The purpose of this paper is to understand the factors which impact upon the consumers’ willingness to utilise company Facebook pages and e-word-of mouth by proposing and testing a conceptual framework which is inspired by theories in marketing and information systems fields. The authors believe that only by applying both theories will provide a more complete understanding of the relationship between brand experience and Facebook. The research model attempts to illustrate the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…For example, other factors that may influence users' emotional value and ultimately their intention to continue their use of online social media brand communities include intimacy with the brand and community identification. Community identification and brand experience have been empirically found to influence users' continuation intentions in prior research on online social media brand communities (Chen et al, 2014;Ho, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, other factors that may influence users' emotional value and ultimately their intention to continue their use of online social media brand communities include intimacy with the brand and community identification. Community identification and brand experience have been empirically found to influence users' continuation intentions in prior research on online social media brand communities (Chen et al, 2014;Ho, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These theoretical frameworks have been mainly used for quantitative investigation of different aspects of user behavior related to online social media brand communities. For example, studies have been conducted on brand loyalty (e.g., Laroche, Habibi, Richard, & Sankaranarayanan, 2012;Kang, Tang, & Fiore, 2014), brand trust (Habibi et al, 2014a), loyalty to online social media brand communities (e.g., Lin & Lu, 2011;Ho, 2014), satisfaction (Gummerus, Liljander, Weman, & Philström, 2012), brand experience (Chen, Papazafeiropoulou, Chen, Duan, & Liu, 2014), word-of-mouth (Chen et al, 2014), intention to join (Muk & Chung, 2014), consumer engagement (e.g., Zheng, Cheung, Lee, & Liang, 2015), and purchase behavior (Ho, 2014). Prior research has concluded that online social media brand communities have a positive influence on user behavior.…”
Section: Online Social Media Brand Communitiesmentioning
confidence: 99%
“…9 studies examine the variable continuance intention/behavior, which addresses the continuous use of a social commerce website, including activities such as revisiting a social commerce website and repurchasing products and/or services from a social commerce website Jang et al, 2013;Kim et al, 2013b;Liang et al, 2011). In a similar way, some researchers use the variable loyalty to measure whether a consumer is interested in continuously using a social commerce website (Anderson et al, 2014;Chen et al, 2014;Gamboa and Gonçalves, 2014;Lee et al, 2012;.…”
Section: Findings On the Outcome Variablesmentioning
confidence: 99%
“…To investigate the consumers' willingness to share shopping information with other consumers on a social commerce website, 9 studies employ the variable information sharing intention/behavior (Chen and Shen, 2015;Cheung et al, 2015;Liu et al, 2013;Liu et al, 2016b;Liu et al, 2014). In this context, some studies also conceptualize this variable as electronic word-of-mouth (eWOM) intention/behavior (Chen et al, 2014;Hudson et al, 2015;Kim and Park, 2013;Shi and Chow, 2015).…”
Section: Findings On the Outcome Variablesmentioning
confidence: 99%
“…For the constructs of the research model, multi-item scales were adopted from the previous studied and modified based on the current research. Perceived community value comprise of five self-administered measured variables adopted from (Chetna, 2016); "fan page engagement "comprises of five items adapted from (Benedikt Jahn, 2012), "fan-page loyalty" comprised of three items adopted from (Hsin, 2014). Consequently, "Purchase Intention" comprises of six items adopted from (Chetna, 2016) .Respondents were asked to rate the questions on five point Likert scales from 1= strongly disagree and 5= strongly agree.…”
Section: A Measurement Instrumentmentioning
confidence: 99%